Estimating the global risk of anthropogenic climate change - Magnan, Alexandre (2021)
The three recent Special Reports of the IPCC provide an opportunity to understand overarching climate risk, as they cover a wide diversity of risks to natural and human systems. Here we develop a scoring system to translate qualitative IPCC risk assessments into risk scores that, when aggregated, describe global risk from climate change. By the end of this century, global climate risk will increase substantially with greenhouse gas emissions compared to today (composite risk score increase of two- and fourfold under RCP2.6 and RCP8.5, respectively). Comparison of risk levels under +1.5 °C and +2 °C suggests that every additional 0.5 °C of global warming will contribute to higher risk globally (by about a third). Societal adaptation has the potential to decrease global climate risk substantially (by about half) under all RCPs, but cannot fully prevent residual risks from increasing (by one-third under RCP2.6 and doubling under RCP8.5, compared to today).